Peruvian Amazonian Spanish and Facebook identity. Linguistic analysis of the page “En la selva dicen” (In the jungle they say) - Pau, Stefano (2019)
This paper proposes a linguistic and sociolinguistic analysis of the Facebook page “En la selva dicen”, an online community that collects and publishes phrases using typical elements of the Amazonian variety of Peruvian Castilian. The purpose of the study is to examine the phonological, morphosyntactic and lexical features of the Peruvian Amazonian Castilian, the ways in which this variety is perceived and changed and, above all, the role of social networks in its preservation and creation of a shared identity, without stereotypes and prejudices.